Use of nano-SiO2 as a preventive maintenance surface treatment in concrete aged by carbonation - Vaca Arciga, Laura; Cruz Moreno, Dulce; FaJardo San Miguel, Gerardo; Orozco Cruz, Ricardo; Tienda Resendez, Francisco (Revista ALCONPAT, 2020)
This study aims to evaluate the use of silicon base (NS) and functionalized (NF) nanoparticles as emerging preventive surface treatment (ST) in reinforced concrete specimens. The specimens were fabricated with a water/cement (w/c) of 0.65 and subjected to a previous aging period through exposure to CO2. Subsequently, two different variants of the treatment were applied by spraying (using a 0.1% dispersion of nanoparticles in water) and then re-applied to carbonation. The carbonation depth and contact angle results indicate that there is an influence between the degree of aging and the efficiency of each treatment.